KAJIAN KRITIS TERHADAP ROMAN LARASATI KARYA PRAMOEDYA ANANTA TOER - Larasaty, Indah; Priyadi, Antonius Totok; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
ABSTRACT This study examines the Larasati romance by Pramoedya Ananta Toer based on critical studies or Critical Discourse Analysis (AWK). The objectives of the study are to describe (a) macro structure (theme), (b) authorâ€™s cognition in creating romance, (c) ideology contained in the Larasati romance by Pramoedya Ananta Toer, and (d) plans for its implementation in Indonesian Language learning in High School. The form of this research is qualitative research with descriptive method. The data used in this research are the quotations of sentences and paragraphs taken from romance. The source of data is Larasati romance by Pramoedya Ananta Toer, the 5th print in 2010. The technique for data obtaining is documentary study and the tool is a note card. Techniques to test the data validity is triangulation and discussion with colleagues. Data analysis is done by analyzing the contents of the text. Based on data analysis, it can be concluded that: (1) Macro structure (theme) is revolution after independence; (2) Author cognition reflected in the Larasati novel by Pramoedya Ananta Toer are: a) artist, b) imprisoned, and c) the names of several characters in a romance such as (a) Chaidir who is meant as Chairil Anwar, (b) Prime Minister who is meant as Soetan Sjahrir or Amir Sjarifuddin Harahap (c) Jassir who is meant as HB Jassin. (3) Political ideology found in the novel Larasati by Pramoedya Ananta Toer are a) racist ideology and b) class conflict ideology. There are three things that present the existence of racist ideology, that are: a) Japan as an invader and Indonesia as colonized; (b) The Dutch as invaders and Indonesia as colonized; and (c) Nica versus Republikein. (4) Considering the curriculum, the purpose of literary learning, how to choose materials, and aspects of readability, the Larasati romance by Pramoedya Ananta Toer can be implemented in Indonesian Language learning in high school especially in XII grade. Recommendation: Larasati romance can be used as material for Indonesian Language learning in high school.Â Keywords: Critical Analysis, romance, macro structure, author cognition, political ideology